Cities of care: A platform for urban geographical care research. Issue 1 (31st October 2019) - Power, Emma R.; Williams, Miriam J.
Abstract: This paper develops an agenda for a broadened conceptualisation of urban caring within geographical research. We open by identifying three existing domains of urban care research: examining spaces of care, materialities of care, and asking who are the subjects of care? We then synthesise three platforms that can be the foundation of a geographical theory and approach to urban care. Drawing from feminist care research and recent keystone pieces on urban caring, we argue, first, that there is a need for a broadened conceptualisation of urban care that emphasises the universal need for care and care that supports human and non‐human flourishing. Second, we propose an expanded scale of urban care analysis that attends to the ways that lives are lived within and through the city. Third, we open up an analysis of where care is located in cities, arguing for the value of locating urban care beyond interpersonal care and care through welfare, to urban governance and planning, markets, and more‐than‐human materialities. We conclude by conceptualising how care might inform utopian dreamings for the just and caring city. We challenge urban geographers to think through the possibilities of care to transform cities.